Improving teachers' capabilities in preparation of Merdeka Curriculum intracurricular learning assessment - Mutiara Sari Dewi; Ika Ratih Sulistiani; Nurca Febri Kartika; Adelia Restu Yulianto (University of Merdeka Malang, 2024)
The implementation of the Merdeka curriculum (IKM) is inseparable from the student assessment process in learning. Teachers are expected not only to be able to plan and carry out learning, but also to be able to conduct assessments to see the achievement of learning objectives. Teachers who are less optimal in assessing the achievement of learning goals for each student will have a fatal impact on early childhood growth and development. Based on this urgency, the purpose of this activity is that RA teachers have the ability to prepare intracurricular learning assessments on the Merdeka curriculum. The community service method used is the Community Based Research (CBR) method with tools using the Rapid Rural Appraisal (RRA) technique. Community service activities were carried out by involving Raudhatul Atfhal teachers of DAU District, stakeholders, and a team of experts as resource persons. The results of the activity showed that there was an improvement in the ability of RA teachers in the preparation of intracurricular assessments with an average of 4.0 indicators or in the very good category. The highest average was seen in the teacher's understanding that the summative assessment was used to determine the achievement of child development of 4.5 or as many as 65 participants (100 percent) stated that they strongly agreed and agreed with the statement. On the other hand, the lowest average (3.5) or as many as 28 participants (43.1 percent) teachers have the understanding that the assessment is used to see children's graduation.